Structural and Functional Features of Developing Brain Capillaries, and Their Alteration in Schizophrenia - Carrier, Micaël; Guilbert, Jérémie; Lévesque, Jean-Philippe; Tremblay, Marie-Ève; Desjardins, Michèle (Frontiers in Cellular Neuroscience, 2021)
Schizophrenia affects more than 1% of the world population and shows a very high heterogeneity in the positive, negative and cognitive symptoms experienced by patients (i.e. hallucinations, delusions, incoherence alogia, affective flattening, anhedonia, avolition, learning and memory deficits). The pathogenic mechanisms underlying this neurodevelopmental disorder are largely unknown although it was proposed to emerge from multiple genetic changes and environmental risk factors. In this work, we explore the potential alterations in the developing blood vessel network leading to schizophrenia by discussing how the vascular network in newborns evolves and what can go wrong with genetic changes and environmental risk factors. Blood vessels, capillaries in particular, constitute a dynamic and complex infrastructure distributing oxygen and nutrients to the brain. During postnatal development, capillaries undergo many structural and anatomical changes in order to form a fully functional mature vascular network. Advanced technologies like magnetic resonance imaging and near infrared spectroscopy are now enabling us now to study how the brain vasculature and its supporting features in humans are established from birth to adulthood. Furthermore, we can investigate the network effect of capillaries on the brain metabolism and the contribution of the entire neurovascular unit including pericytes, endothelial cells, astrocytes and microglia, to brain function and behavior. This analysis in specific regions altered in schizophrenia such as the prefrontal cortex provides insight into the evidence that schizophrenia could be considered a neurovascular disorder.